Clinical course of a cohort of children with non‐neurogenic daytime urinary incontinence symptoms followed at a tertiary center - Adrienne Lebl; Simone Nascimento Fagundes; Vera Hermina Kalika Koch (Brazilian Society of Pediatrics, 2016)
Objective: To characterize a cohort of children with non‐neurogenic daytime urinary incontinence followed‐up in a tertiary center. Methods: Retrospective analysis of 50 medical records of children who had attained bladder control or minimum age of 5 years, using a structured protocol that included lower urinary tract dysfunction symptoms, comorbidities, associated manifestations, physical examination, voiding diary, complementary tests, therapeutic options, and clinical outcome, in accordance with the 2006 and 2014 International Children's Continence Society standardizations. Results: Female patients represented 86.0% of this sample. Mean age was 7.9 years and mean follow‐up was 4.7 years. Urgency (56.0%), urgency incontinence (56.0%), urinary retention (8.0%), nocturnal enuresis (70.0%), urinary tract infections (62.0%), constipation (62.0%), and fecal incontinence (16.0%) were the most prevalent symptoms and comorbidities. Ultrasound examinations showed alterations in 53.0% of the cases; the urodynamic study showed alterations in 94.7%. At the last follow‐up, 32.0% of patients persisted with urinary incontinence. When assessing the diagnostic methods, 85% concordance was observed between the predictive diagnosis of overactive bladder attained through medical history plus non‐invasive exams and the diagnosis of detrusor overactivity achieved through the invasive urodynamic study. Conclusions: This subgroup of patients with clinical characteristics of an overactive bladder, with no history of urinary tract infection, and normal urinary tract ultrasound and uroflowmetry, could start treatment without invasive studies even at a tertiary center. Approximately one‐third of the patients treated at the tertiary level remained refractory to treatment.